(untitled) (Acta Scientiarum. Biological Sciences, 2018)
The present study aimed to evaluate the larvicidal effect of aqueous leaf extract from Jatropha mollissima on the larvae of Aedes aegypti and analyze its cytotoxic and genotoxic activity in the Allium cepa test. Larvae of the mosquito were exposed to the negative and positive controls (distilled water and diflubenzuron, 0.003 mg mL-1, respectively) and to leaf extract concentrations of 0.001, 0.005, 0.01, 0.02, 0.04, 0.06, 0.08 and 0.1 mg mL-1. The mortality rate was evaluated every 24 hours over five days. For the cytotoxic and genotoxic analyses, roots of A. cepa were exposed to the negative (distilled water) and positive control (trifluralin, 0.84 ppm) and to different leaf extract concentrations (0.01, 0.1, 1 and 10 mg mL-1) for 24 hours. The statistical analyses were performed by Kruskal-Wallis test (p < 0.05). The leaf extract presented promising larvicidal activity at the concentrations of 0.08 and 0.1 mg mL-1, and none of the concentrations evaluated in A. cepa exhibited cytotoxic or genotoxic effect. Since the larvicidal action of J. mollissima and the absence of cellular toxicity have been demonstrated, further studies are recommended to determine the mechanism of action of the extract as a possible natural larvicide.